Effect of Land Use on Soil Water Storage in the Effective Depth (0–60 cm) Using the Water Balance Method - Muara Dhika; Bakti Wisnu Widjajani; Maroeto Maroeto (The University of Lampung, 2025)
Land use changes significantly impact groundwater storage, which is crucial for maintaining ecosystem balance and supporting agriculture. This study aims to evaluate groundwater storage capacity across various land uses in the Gunting Sub-watershed, Wonosalam District, Jombang Regency, East Java. Field surveys and soil sampling were conducted across three land use types: pine-coffee agroforestry, pine monoculture, and annual crops at effective soil depths (0-60 cm). The study was conducted using a water balance method and lasted for one year, from August 2022 to July 2023. Water balance components consisting of effective rainfall, surface runoff, percolation, and evapotranspiration, as well as soil properties such as organic carbon content, porosity, and texture, were analyzed. The results showed that agroforestry had the highest water storage (370,863.44±176.67 mm/year), followed by pine monoculture (307,153.36±229.98 mm/year), and annual crops (239,497.30±222.26 mm/year). Statistical tests showed that differences between land uses were not significant (p > 0.05). Organic matter content was the dominant factor influencing soil water storage (R² = 0.9189), followed by porosity (R² = 0.3019) and clay fraction (R² = 0.0172). All land use types showed a positive water balance throughout the year, with peak water storage occurring in February–May.